Analisis Permintaan Telur Ayam Ras Di Kota Padang Dan Faktor Yang Mempengaruhinya - Fitrini Fitrini; Andri Andri; A.N. Yanti (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2006)
The aim of this research was to study the market demand of chicken egg in relation to some variables that influence the egg consumption of people in Padang city. Some factors considered affecting egg demand included: egg price, price of chicken meat and fish, number of population and people income. Data on egg demand and their affecting factors were collected from literatures and reports published from the year of 1983-2002. Explanatory Research Design was applied to explain the relationship between egg demand as dependent variable and factors affecting the demand as independent variables. The data was the analyzed by non linear regression model. Results of this research showed that price of egg, chicken meat and fish as well as number of population and income influenced significantly egg demand in Padang City ( R2 = 0,888).